Occurrence of Relative Bradycardia and Relative Tachycardia in Individuals Diagnosed With COVID-19 - Natarajan, Aravind; Su, Hao-Wei; Heneghan, Conor (Frontiers in Physiology, 2022)
The COVID-19 disease caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has become one of the worst global pandemics of the century. Wearable devices are well suited for continuously measuring heart rate. Here we show that the Resting Heart Rate is modified for several weeks following a COVID-19 infection. The Resting Heart Rate shows 3 phases: (i) elevated during symptom onset, with average peak increases relative to the baseline of 1.8% (3.4%) for females (males), (ii) decrease thereafter, reaching a minimum on average ~ 13 days after symptom onset, and (iii) subsequent increase, reaching a second peak on average ~ 28 days from symptom onset, before falling back to the baseline ~ 112 days from symptom onset. All estimates vary with disease severity.